2012
DOI: 10.1530/eje-11-0749
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive performance after postoperative pituitary radiotherapy: a dosimetric study of the hippocampus and the prefrontal cortex

Abstract: Objective: The hippocampus and prefrontal cortex (PFC) are important for memory and executive functioning and are known to be sensitive to radiotherapy (RT). Radiation dosimetry relates radiation exposure to specific brain areas. The effects of various pituitary RT techniques were studied by relating detailed dosimetry of the hippocampus and PFC to cognitive performance. Methods: In this cross-sectional design, 75 non-functioning pituitary macroadenoma (NFA) patients (61G10 years) participated and were divided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 36 publications
2
17
0
Order By: Relevance
“…Few studies attempt to evaluate the cognitive effects of RT in this setting, but the best study on this subject showed no detrimental effect. 12 In our series, 30 patients (26%) with clinical tumor control developed a pituitary hormone deficiency requiring medical management. It is difficult to separate the influence of RT from surgery and the influence of the tumor, but it is reasonable to assume that RT compromises pituitary function.…”
Section: Complications From Rtmentioning
confidence: 70%
“…Few studies attempt to evaluate the cognitive effects of RT in this setting, but the best study on this subject showed no detrimental effect. 12 In our series, 30 patients (26%) with clinical tumor control developed a pituitary hormone deficiency requiring medical management. It is difficult to separate the influence of RT from surgery and the influence of the tumor, but it is reasonable to assume that RT compromises pituitary function.…”
Section: Complications From Rtmentioning
confidence: 70%
“…WMLs and cerebral atrophy) are unknown and have not yet been investigated. Nevertheless, several studies reported on cognitive function [8][9][10]. Previously, we found no major influence of RT on cognition in NFA patients treated with RT compared to those treated with surgery-alone [8,9].…”
mentioning
confidence: 56%
“…Previously, we found no major influence of RT on cognition in NFA patients treated with RT compared to those treated with surgery-alone [8,9]. Furthermore, a dose-response relationship, by relating detailed radiation dosimetry to the temporal lobes, hippocampi and the prefrontal cortex, with cognition could not be established [10]. In addition, we showed that postoperative RT was not associated with an increased incidence of second tumours, stroke or mortality compared to pituitary adenoma patients treated with surgery-alone [11,12].…”
mentioning
confidence: 80%
“…Gondi et al (47) demonstrated that biologically equivalent doses in 2-Gy fractions (EQD2) delivered to 40% of the bilateral hippocampi (D40%) O7.3 Gy (assuming an a/b ratio of 2 Gy) were associated with long-term impairment in list-learning delayed verbal recall in 18 patients receiving FSRT for benign brain tumors. In contrast, Brummelman et al (48) found no significant differences in cognitive performance among 30 patients who received radiotherapy for NFPA when mean doses up to 15.2 Gy were given to 50% of the hippocampal volume. Delivering a mean dose of 10 Gy to the bilateral hippocampi, we observed no clinically apparent neurocognitive deterioration over time; however, the lack of formal neurocognitive testing and the relatively short follow-up do not allow a definitive conclusion to be drawn.…”
Section: Discussionmentioning
confidence: 87%